The Effect of Return on Assets and Debt to Equity Ratio on Tax Aggressivity: Total Asset as Moderating Variable - Aliftika Cipta Dewi; Rieke Pernamasari (Jurnal Riset Akuntansi Terpadu, 2022)
This study aims to determine the effect of return on assets (ROA) and debt to equity ratio (DER) on tax aggressiveness with total asset as moderating in manufacturing companies Listed on the indonesia stock exchange (IDX) in 2019 - 2021. This research is a quantitative research type and the sample was based on the purposive sampling method with a total sample of 174. methode analysis used is linear regression analysis. The results partial test results with the t-test showed that ROA had a negative effect on tax aggressiveness, and DER had a positive effect on tax aggressiveness. total asset strengthens the effect of ROA on tax aggressiveness but total asset weaken the effect of DER on tax aggressiveness.